Tendense in die interpretasie van godsdiensregte - Swanepoel, J (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
This study attempts to trace the main tendencies in South African jurisprudence with regard to the interpretation and adjudication of religious rights in the new constitutional dispensation. This is done by way of an analysis of the legal framework governing religious rights and by a discussion of the dicta of the Courts on how adjudication of religious rights should best be undertaken. An exposition is given of the main positions taken by the Courts thus far with reference to the Lawrence, CESA and Prince cases. Particular attention is pad to the values guiding constitutional interpretation and adjudication of religious rights. This is done with a view to considering the possibility of predicting whether litigants who approach the courts to uphold their religious rights have a reasonable chance of succeeding with their claims.